Analysis of the Concept of "Digital Financial Literacy" in the High School Economics Curriculum: An Exploratory Study of Impacts and Challenges - Annisaturrahmi (eL - BASIRAH : JURNAL PENDIDIKAN TEKNOLOGI INFORMASI, 2025)
The SMA Economics curriculum has not yet integrated Digital Financial Literacy well , while students as a digital native generation actively use various modern financial platforms. This creates a dangerous gap where they are technically proficient but have little understanding of risk and the concepts behind it. As a result, students are vulnerable to digital fraud, online loan defaults, and irrational investment decisions. The type of research uses a qualitative approach with the type of library research ( library research ). The data collection technique applied is the documentary study technique. The research results show that: 1). The Literacy Gap: Between Technology Ability and Students' Digital Financial Understanding is that there is a dangerous paradox in high school students: although they are skilled in using digital financial applications such as e-wallets and investment platforms, their understanding of basic concepts and risks is very minimal. 2). Teacher Challenges and Curriculum Infrastructure Limitations is that on the educator's side, the integration of digital financial literacy is hindered by three main challenges. First, the rigid curriculum still focuses on traditional financial institutions without enough space for FinTech material. Second, the majority of teachers feel that they have a stutter in technology and do not have sufficient competence and teaching materials. Third, school policies such as banning the use of mobile phones and the inequality of digital infrastructure make it increasingly difficult to apply contextual learning. 3). Integration Strategy: Designing a Contextual and Adaptive Digital Financial Literacy Framework for Generation Z is that the solution offered is integration through an infusion approach into existing topics, such as discussing FinTech in the chapter on financial institutions or the psychology of impulse buying in the marketplace in the chapter on consumption.